Intra- and Intersubject Variability in Audiometric Measures and Loudness Judgments in Older Listeners with Normal Hearing - Hawley, Monica L.; Sherlock, LaGuinn P.; Formby, Craig (Seminars in Hearing, 2017)
This research was to document intra- and intersubject variability in measures of pure tone thresholds, loudness discomfort levels, and the Contour test of loudness for tonal and speech stimuli across 8 to 10 repeated test sessions over a period of almost 1 year in a group of 11 normal-hearing, older middle-aged adults (39 to 73 years, mean of 56 years). The measured pure tone thresholds and loudness discomfort levels were determined to be stable across sessions, with variability on the order of 5 dB. The categorical judgments for the Contour test for both warbled tones and spondaic speech stimuli decreased over time in level required for categories greater than comfortable. This result contrasts with reports of a slight increase over time when young, normal-hearing adults were tested in comparable measures. The intrasubject variability in the Contour test results was greatest for the 4,000-Hz tonal stimulus for which the largest time effects were observed. The intersubject variability was typically greater than the intrasubject variability and typically increased as the loudness category increased, with some exceptions. The results from this study can be used to aid in power and sample size analyses using these measures in future studies designed to compare effects of treatments based on changes in loudness judgments over time.
Keywords: Sound tolerance; loudness discomfort level; pure tone threshold; categorical loudness judgments